Enhancement of fertility and libido in male sprague dawley rats following the administration of aqueous extract of Lunasia amara - Nor-Raidah, R.; Mahanem, M.N. (Penerbit Universiti Kebangsaan Malaysia, 2015)
Lunasia amara (sanrego) is a folk medicinal herb which has been consumed to treat male fertility and libido. This study aims to investigate the effect of L. amara aqueous extract on libido, sperm quality, serum testosterone level, antioxidant enzyme activity and histology of testis. Two groups (n=6) were given distilled water (control) and aqueous extract of L. amara at a dose of 60 mg/kg/body weight respectively daily for 42 days. On day 43, rats were subjected to sexual behavioural test before sacrificed for sperm quality and testosterone analysis. Cauda epididymis was isolated for sperm quality analysis whereas serum was collected to determine the level of testosterone. Histology of testes and antioxidant enzyme activities were also investigated. Results showed the administration of L. amara aqueous extract significantly (p<0.05) increased the mount frequency compared to normal rats. Sperm count, motility, viability, testosterone level and testicular antioxidant enzyme activities in treated rats showed significantly (p < 0.05) increased compared to control. Section of seminiferous tubules in treated group showed the increasing of spermatozoa density compared to the normal group. In conclusion, L. amara aqueous extract is effective in improving libido, sperm quality, serum testosterone level and testicular antioxidant enzyme activities while increased the density of spermatozoa.